1985
DOI: 10.1149/1.2114315
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical and Corrosion Study of n‐Type SnSSe

Abstract: Single crystals of n-type SnS~Se2_x (x = 1.04) obtained both by transport and Bridgman methods exhibit an energy gap of 1.53 eV. The flatband potential is pH dependent, and its values in acidic and alkaline solutions are, respectively, 0.06 and -0.6V (SCE). In the dark, SnSSe is stable in acidic medium, but the stability decreases as pH increases. It is also unstable in acidic solutions containing the oxidizing form of a redox reagent with a sufficiently positive redox potential (ca. more positive than 0.8V/SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The drop in the carrier concentration in the films that were deposited at 425 °C and 450 °C might be attributed to the appearance of the second phase. The carrier concentration for the SnSSe deposited at 400 °C was two orders of magnitude higher than the one obtained by Perluzzo et al and compared favorably with the results of Fotouhi and Patel et al [11,32,34]. Hall and Seebeck coefficients of these materials showed that electron is the majority charge carrier; however, some fluctuations were observed in the films deposited at 425 °C and 450 °C.…”
Section: Electrical Propertiessupporting
confidence: 84%
“…The drop in the carrier concentration in the films that were deposited at 425 °C and 450 °C might be attributed to the appearance of the second phase. The carrier concentration for the SnSSe deposited at 400 °C was two orders of magnitude higher than the one obtained by Perluzzo et al and compared favorably with the results of Fotouhi and Patel et al [11,32,34]. Hall and Seebeck coefficients of these materials showed that electron is the majority charge carrier; however, some fluctuations were observed in the films deposited at 425 °C and 450 °C.…”
Section: Electrical Propertiessupporting
confidence: 84%
“…19 Bulk SnS 2 crystals (usually representing a bandgap of 2.1-2.31 eV) have long been explored for possible applications in photovoltaics and photoelectrochemistry. 20,21 In addition, recent evidence has already pointed out the fascinating progress in applying 2D SnS 2 structures in lithium ion batteries, 22 eld-effect devices 23 and photodetectors, 24 benetting from the simple exfoliation from bulk crystals and the controlled bottom-up synthesis. 25,26 In particular, due to a considerable absorption coefficient (10 6 cm À1 ), 27 light sensors using 2D SnS 2 structures (most are obtained by CVD) exhibit superior UV-vis sensing performance such as high responsivity and good stability.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of this family, tin disulfide (SnS 2 ) was previously investigated in the bulk form for various applications. [28][29][30][31][32][33][34] After the emergence of novel 2D materials and improved production methods such as chemical vapor deposition, chemical and mechanical exfoliation, thinner structures of SnS 2 were synthesized for different applications. For example, a few nanometer-thick hexagonal SnS 2 was used for lithium storage in battery applications.…”
Section: Introductionmentioning
confidence: 99%